Increasing Skills for Processing Rainwater into Clean Water using the Electrolysis Method - Qudus, Nur; Sugiyarto, Bambang; Harianingsih, Harianingsih; Kristanto, Virgiawan Adi; Erliana, Savira Rinda; Pangestu, Indra Sakti; Ubay, Isnina Noor; Afidah, Asti Dwi (Jurnal Abdimas, 2023)
The aim of community service activities from the UNNES Civil Engineering and Chemical Engineering Department Collaboration Team in Patemon is to improve the community's skills in processing rainwater so that it is suitable for consumption using the electrolysis method which has been tested for effectiveness and quality in the laboratory first. The Patemon area is an area where the water source comes from wells, has a slope of 10-45% so that during the dry season there is a shortage of water flow. The very high rainfall in Patemon, an average of 1853 mm/month, has the potential to be processed into clean water as a solution for availability in the dry season. The methods used for this service activity include field observation and coordination, training to improve skills in improving rainwater processing using electrolysis, monitoring and evaluating service results. The results obtained from this activity show that rainwater electrolysis is an appropriate alternative for providing clean water in the Patemon area. The education provided by the UNNES service team has increased the community's knowledge and skills in rainwater processing from 8% to 35%. Increased knowledge regarding rainwater harvesting from the system and working principles of rainwater electrolysis from 0% to 85%. Enthusiasm and interest in implementing activities reached 98%.